PENINGKATAN PRODUKTIVITAS LAHAN MELALUI PEMANFAATAN BIOMAS TANAMAN Flemengia congesta UNTUK BUDIDAYA TANAMAN JAGUNG DI DAERAH TRANSMIGRASI KURO TIDUR, BENGKULU - Mulyono, Daru (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
The objective of the research is to know the effect of using biomass and combinationÃ‚Â between biomass and dolomit to the land fertility with regard to corn production. TheÃ‚Â research used Complete Randomized Design with One Way Analysis of Variance,Regression, and Correlation in order to know the effect of treatment to the land fertility.The research was carried out in Wonoharjo Village, Unit VIII Kuro Tidur TransmigrationÃ‚Â area, Bengkulu, during three planting seasons from 2003 to 2004. The results of theÃ‚Â research showed that biomass from prunning of the hedgerows Flemengia congestaÃ‚Â was significant to land fertility through improvement of nutrients availability, increasingÃ‚Â pH, decreasing availability of aluminium (Al). The effect of biomass treatment into theÃ‚Â soil to a high of 5.0 ton/ha will increase average corn production from 22.256 kw/haÃ‚Â (dry grain) to 37.433 kw/ha or increase 68.19 %, whereas the effect of organic matterÃ‚Â 5.0 ton/ha combined with dolomit 2.5 ton/ha will increase average corn production fromÃ‚Â 22.256 kw/ha to 47.611 kw/ha or increase 113.92 %. The effect of biomass 10.0 ton/haÃ‚Â combined with dolomit 2.5 ton/ha will increase average corn production from 22.256kw/ha to 50.789 kw/ha or increase 128.20 %.